Pendidikan Karakter Religius Tokoh Soekarno dalam Novel Kuantar ke Gerbang Karya Ramadhan K.H - Al Gadri, Henri Henriyan (Jurnal Artikula, 2019)
This research examines the religious character education of Soekarno in the novel "Kuantar ke Gerbang" by Ramadhan K.H. The purpose of this study is to explain the values ​​of character education that can be taken from the figure of Soekarno through any stories or events contained in the novel. This research method uses descriptive analysis by trying to describe and translate objects as they are. The results of this study are the values ​​of character education from Sukarno's figures in the form of religious values, honesty, tolerance, national spirit, love for the motherland, fond of reading, hard work, independent, democratic, respect for achievement, communicative, love for peace, curiosity environmental care, social care and responsibility. The results of this study are expected to broaden the treasury of science, especially in the field of education in Indonesian Language and Literature in schools in particular and the general public.